Expanding the role of Medical Colleges in RNTCP towards End TB strategy: Scope and Challenges - Purty, Anil J; Anandan, Velavan (Indian Journal of Community Health, 2018)
Tuberculosis (TB) remains a major global public health problem and it has been the leading cause of death due to an infectious agent in the past five years. During the last decade, the global and national efforts have been focused on achieving the targets set by the Millennium Development Goals (MDGs) and the Stop TB Strategy to reduce the burden of tuberculosis disease. In 2016, the Sustainable Development Goals (SDG) framework of goals, targets and indicators were adopted and in line with it End TB Strategy was unanimously endorsed by all WHO member states for the period of 2016 – 2035 (1). Based on these global efforts, India which accounts for about one quarter of world TB cases has formulated the National Strategic Plan (NSP) for TB elimination 2017-2025 to guide the activities of all stakeholders whose work is relevant to TB elimination in India.